Review of the Current Situation of Postoperative Pain and Causes of Inadequate Pain Management in Africa - Gao L; Mu H; Lin Y; Wen Q; Gao P (Journal of Pain Research, 2023)
Lejun Gao,1,* Huaixin Mu,2,* Yun Lin,1 Qingping Wen,1,3 Peng Gao1 1Department of Anesthesiology, First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China; 2Emergency Department, Shenyang Children’s Hospital, Shenyang, People’s Republic of China; 3Department of Anesthesiology, Dalian Medical University, Dalian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng Gao; Qingping Wen, Department of Anesthesiology, First Affiliated Hospital of Dalian Medical University, NO. 222 Zhongshan Road, Dalian, 116011, People’s Republic of China, Tel/Fax +86 411 86110440, Email dalianpeople@163.com; dmuwqp@163.comAbstract: Postoperative pain is one of the most prevalent complications following surgery, and more than 47% of surgical patients endure postoperative discomfort worldwide. In Africa, due to resource shortages and other issues, postoperative pain is substantially more common when compared to developed countries. Severe postoperative pain has many negative effects, including possibly death, which can burden both individuals and society as a whole. Therefore, effectively controlling postoperative pain is becoming increasingly important. To enhance the effectiveness of future pain management, a thorough analysis of the current reasons for inadequate postoperative pain management is necessary. In this article, the present situations of occurring postoperative pain, children’s postoperative pain, and pain management in Africa are reviewed, based on relevant and recent literature. In particular, the reasons for inadequate postoperative pain management in Africa are detailed in this article from five perspectives: the inadequate assessment of postoperative pain, the knowledge gap among medical professionals, the patients’ misconceptions, the scarcity of resources, and the lack of medications. Additionally, we offer appropriate solutions following various factors.Keywords: Africa, postoperative pain, pain management, analgesia, pain in children, pain assessment